MRO WIP Demystified: Management of Work-In-Process Inventory in the Maintenance, Repair and Overhaul (MRO) Business - Mahn, Georg Burkhard (2013)
This dissertation highlights pitfalls in transferring WIP management approaches from Manufacturing to MRO and identifies which WIP management approaches from manufacturing are beneficial in the MRO business. To do so a comprehensive framework to compare Manufacturing and MRO businesses is developed. The conclusion is that both business operations are similar in a number of aspects, but the performance and value determining mechanisms are very different. Therefore the basic operation paradigms are (ideally) different. Some WIP Management practices from Manufacturing harm MRO, while some Manufacturing Don'ts are beneficial or neutral. Complementary to the above an analysis on MRO unique practices is conducted. A scenario model is developed to provide the data to evaluate the impact of these practices on WIP, Cash and customer perceived performance. The combination of practices which achieves the highest customer satisfaction is neither correlated with the lowest WIP nor necessarily with the highest profit. The insights from both pieces of analysis are combined into a MRO WIP Management Framework which includes suggestions for a production/ operation control system, policies derived from manufacturing, improvement techniques and “Six Golden MRO Policies” as guidelines for practitioners.